FULL DIALLEL CROSSES AND ESTIMATION GENETICPARAMETERS FOR SOME QUALITATIVE CHARACTERSOF TOBACCO HYBRIDS IN GREEN HOUSE - Al-Shamma, Laith; Baktash, Fadel (Iraqi Journal of Science, 2024)
Full diallel crosses conducted to develop tobacco hybrids using three cultivars;Corjo (A), Sumer48 (B) and Croillo (C), during 2004, Hybrid trail carried out in thegreen house using Randomized Complete Block Design with 3 parents, 6 hybridsand 2 control, Habana and CV. 48.Significant differences were found among parentsand hybrids in studied characters except necotin and ash percentages. The crosses(AxB) and (BxC) superior in pH (6.71 & 6.37), while the crosses (AxB) superior insugar percentage, the reciprocal hybrid (BXA) had highest burne speed (0.101mm/sec.). Genetic parameters analysis revealed, that average degree of dominancewere higher than one, broad sence heratibiliy, also highest, narrow sence heratibilitywere lowest. It was recommended hybridization method in the improvement of pH,burne speed and sugar percentage of tobacco, using best hybrid (AXB).